The use of public utility facility entered into the register of monuments to fulfill the contemporary occupancy function - Brzozowski, Mieczysław; Święcicka-Brzozowska, Katarzyna (Budownictwo i Architektura / Civil and Architectural Engineering, 2017)
This article describes the concept of the use of Hospital-almshouse in Sawin, considered a historic object of public utility, for contemporary occupancy function. In the introduction the author presents the history of the object created on the basis of both studies as well as documents and expert opinions of the competent authorities and administrative units. The next part features the present building condition of the facility made on the basis of a detailed survey conducted with the use of the latest specialist equipment. The final part provides the assumptions of the project aiming at the revitalization of the object which will serve the Regional Society of Sawin Commune in order to achieve its statutory purposes.